2000
DOI: 10.1159/000024317
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Human IgE Mediated by <i>Schistosoma mansoni</i>

Abstract: Background: IgE-mediated mechanisms are important in protection against helminth parasites. However, schistosomes are long-lived in mammalian hosts, presumably as a result of immune evasion strategies. We sought evidence for one such strategy, namely specific cleavage of host IgE. Methods: Human IgE, IgA and IgG were incubated with extracts from cercarial and schistosomular stages of Schistosoma mansoni or with schistosomular culture supernatants. The resulting products were analysed by Western blotting with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…The same skin-stage schistosome ES directs DCs to drive Th2 responses in vivo [37]. This ES contains abundant proteases, including several elastases that facilitate parasite skin penetration [38], and can cleave host IgE antibodies [39]. The presence of multiple isoforms of cercarial elastase and a metalloprotease was confirmed by proteomics of cultured parasites [40,41], and by proteomic analysis of human skin traversed by invading cercariae [42].…”
Section: Functional and Molecular Analyses Of Helminth Productsmentioning
confidence: 99%
“…The same skin-stage schistosome ES directs DCs to drive Th2 responses in vivo [37]. This ES contains abundant proteases, including several elastases that facilitate parasite skin penetration [38], and can cleave host IgE antibodies [39]. The presence of multiple isoforms of cercarial elastase and a metalloprotease was confirmed by proteomics of cultured parasites [40,41], and by proteomic analysis of human skin traversed by invading cercariae [42].…”
Section: Functional and Molecular Analyses Of Helminth Productsmentioning
confidence: 99%
“…This cleavage can be inhibited by serine protease inhibitors. This indicates that during the establishment of mature infections, an elastase-like serine protease helps the parasite to evade IgE-mediated protective reactions [ 46 ]. A recent study using a highly purified SmCE found that these SmCE cleave IgE at solvent-exposed interdomain regions of the IgE-Fc.…”
Section: Trematode Serine Proteasesmentioning
confidence: 99%
“…SmCE could have a role in immune evasion, as a highly purified SmCE was able to cleave IgE and other key molecules involved in immune regulation [101]. The use of serine protease inhibitors prevented IgE cleavage by cercariae and schistosomula extracts in a previous study, indicating that this could be a promising path for therapeutic strategies [102].…”
Section: Peptidasesmentioning
confidence: 94%